Development of Regional Innovation Potential under the Influence of the Oil and Gas Industry - I. L. Beilin (Мир новой экономики)
Relevance In the context of a nationally oriented economy, the formation of innovative potential for regional economic development based on the industrial determinant of the budget-forming oil and gas industry is the most important driver of structural and technological shifts, modernization of modern industrial production and “energy transition 4.0” taking into account the challenges of the latest geopolitical reality. The economic production efficiency of an oil and gas region has a high impact on the functioning of the national economic system due to a numbeeconomy, contribute significantly to the formation of regional budgets, meanwhile, sustainability and energy security of the economy of oil and gas regions to overcome external shocks can be supported by innovative interregional and intersectoral industrial clusters with “anchor” enterprises for hydrocarbon extraction and processing. The objective of the study is to assess the formation problems and disclose the innovative potential of the regional oil and gas industry as a set of scientific and technological achievements and investment climate of the oil and gas region in the conditions of transformation of the global energy balance, technological and financial independence, sanctions restrictions on oil and gas exports. The result of the study is the development of an equilibrium cyclic model of the system of priority conditions and optimal results of formation and disclosure of the innovation potential of regional development under the influence of the industrial determinant of the budget-forming oil and gas industry and aimed at maintaining the economic resilience of the region.